2013
DOI: 10.1126/science.1241146
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Among Memory B Cells: Origin, Consequences, and Utility

Abstract: Immunological memory is the residuum of a successful immune response that in the B cell lineage comprises long-lived plasma cells and long-lived memory B cells. It is apparent that distinct classes of memory B cells exist, distinguishable by, among other things, immunoglobulin isotype, location, and passage through the germinal center. Some of this variation is due to the nature of the antigen, and some appears to be inherent to the process of forming memory. Here, we consider the heterogeneity in development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
172
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(179 citation statements)
references
References 103 publications
5
172
1
1
Order By: Relevance
“…Analysis of double-negative mBCs, CD19 (37,38). The origin, antigenic specificity, and tissue location of double-negative mBC populations are still under debate (45,46). Our analyses did not reveal a complete exclusion or an exclusive enrichment of one or the other mBC population within any specific tissue and, therefore, is consistent with the migrating nature of all mBC subsets.…”
Section: Discussionsupporting
confidence: 65%
“…Analysis of double-negative mBCs, CD19 (37,38). The origin, antigenic specificity, and tissue location of double-negative mBC populations are still under debate (45,46). Our analyses did not reveal a complete exclusion or an exclusive enrichment of one or the other mBC population within any specific tissue and, therefore, is consistent with the migrating nature of all mBC subsets.…”
Section: Discussionsupporting
confidence: 65%
“…HIVspecific B cell responses were also clearly distinct from responses against the non-HIV antigens influenza and tetanus, the latter of which was comparatively enriched within the resting memory B cell subset. However, we also found that resting memory B cells, which are abundant in healthy uninfected individuals and depleted in HIV disease (21,22,46), accounted for a relatively greater proportion of the HIV-specific response in infected individuals who maintained low plasma viremia and low immune activation either naturally or as a result of the initiation of ART. Furthermore, the response against the highly immunogenic yet generally poorly neutralizing site, CoRbs, was strongest in early HIV infection, contrasting with a less rapid response against the less immunogenic yet more neutralizing site, CD4bs.…”
Section: Discussionmentioning
confidence: 55%
“…production, or differentiation into antibody-secreting cells (8)(9)(10). Memory B cells can also express different antibody isotypes that fulfill diverse spatiotemporal and pathogen-specific roles upon secretion (11,12).…”
Section: Introductionmentioning
confidence: 99%